Abilities of berberine and chemically modified berberines to interact with metformin and inhibit proliferation of pancreatic cancer cells. (August 2019) - Akula, Shaw M.; Candido, Saverio; Libra, Massimo; Abrams, Stephen L.; Steelman, Linda S.; Lertpiriyapong, Kvin; Ramazzotti, Giulia; Ratti, Stefano; Follo, Matilde Y.; Martelli, Alberto M.; Murata, Ramiro M.; Rosalen, Pedro L.; et al.
Abstract: Pancreatic cancer is devastating cancer worldwide with few if any truly effective therapies. Pancreatic cancer has an increasing incidence and may become the second leading cause of death from cancer. Novel, more effective therapeutic approaches are needed as pancreatic cancer patients usually survive for less than a year after being diagnosed. Control of blood sugar levels by the prescription drug metformin in diseases such as diabetes mellitus has been examined in association with pancreatic cancer. While the clinical trials remain inconclusive, there is hope that certain diets and medications may affect positively the outcomes of patients with pancreatic and other cancers. Other natural compounds may share some of the effects of metformin. One "medicinal" fruit consumed by millions worldwide is berberine (BBR). Metformin and BBR both activate AMP-activated protein kinase (AMPK) which is a key mediator of glucose metabolism. Glucose metabolism has been shown to be very important in cancer and its significance is increasing. In the following studies, we have examined the effects of metformin, BBR and a panel of modified BBRs (NAX compounds) and chemotherapeutic drugs on the growth of four different human pancreatic adenocarcinoma cell lines (PDAC). Interestingly, the effects of metformin could be enhanced by BBR and certain modified BBRs. Upon restoration of WT-TP53 activity in MIA-PaCa-2 cells, an altered sensitivity to the combination of certain NAX compounds and metformin was observed compared to the parental cells which normally lack WT-TP53. Certain NAX compounds may interact with WT-TP53 and metformin treatment to alter the expression of key molecules involved in cell growth. These results suggest a therapeutic approach by combining certain pharmaceutical drugs and nutraceuticals to suppress the growth of cancer cells.